Effects of Acute Hyperthermia on the Thermotolerance of Cow and Sheep Skin-Derived Fibroblasts - Islam M. Saadeldin; Ayman Abdel-Aziz Swelum; Adel M. Zakri; Hammed A. Tukur; Abdullah N. Alowaimer (Animals, 2020)
This study was conducted to compare the effects of acute hyperthermia (45 °C for 4 h) on the viability, proliferation, and migratory activity through wound-healing assays of cow and sheep fibroblasts. The study examined the effects on primary cultures and first passage skin-derived fibroblasts. Relative quantification of HSP70, HSP90, P53, BAX, BCL2, and BECN1 was investigated after normalization to housekeeping genes GAPDH and beta-actin. The results revealed that cultured cow primary fibroblasts exhibited increased viability and reinitiated cell migration to close the cell monolayer scratch earlier than sheep cells. Similar patterns were observed in the first passage fibroblasts, with severe effects on sheep cells. Both cow and sheep cells exhibited decreased cell viability and failed to regain migratory activity after re-exposure of recovered heat-shocked cells. Effects of hyperthermia on sheep cells were potentiated by cell cryopreservation. The qPCR results showed that cow cells significantly increased HSP70 and HSP90 expression, which decreased the elevation of P53, and ameliorated the effects of the increased BAX/BCL2 ratio. The results provide a paradigm to compare thermotolerance among different animal species and revealed that trypsin could be an additional stress, which potentiates the effects of heat shock in in vitro experiments.